Hubungan antara Efikasi Diri dengan Kemampuan Berpikir Kritis IPA Siswa - Nurul Ilmi Muhammad; Muhammad Amran; Satriani DH (Jurnal Pendidikan Dasar dan Menengah (Dikdasmen), 2021)
The problem in this study is that there are still students who have not been able to develop critical thinking skills because of their lack of self-confidence. This study is a quantitative study with correlation design that aims to determine correlation between self-efficacy and critical thinking skills in science in high grade students of SDN 2 Kulo. The results showed there was a significant relationship between self-efficacy and the ability to think critically in science in high grade students of SDN 2 Kulo with a tcount(2.9130) is greater (>) the value of ttable(1.68023) which means H0 is rejected and H1 is accepted. Based on analysis of the data above, it can be concluded thatIf students have good self-efficacy, their critical thinking skills are also good. From these conclusions, impact resulting from this study is known that if the self-efficacy is good, it will increase students' critical thinking skills in science.The problem in this study is that there are still students who have not been able to develop critical thinking skills because of their lack of self-confidence. This study is a quantitative study with correlation design that aims to determine correlation between self-efficacy and critical thinking skills in science in high grade students of SDN 2 Kulo. The results showed there was a significant relationship between self-efficacy and the ability to think critically in science in high grade students of SDN 2 Kulo with a tcount(2.9130) is greater (>) the value of ttable(1.68023) which means H0 is rejected and H1 is accepted. Based on analysis of the data above, it can be concluded thatIf students have good self-efficacy, their critical thinking skills are also good. From these conclusions, impact resulting from this study is known that if the self-efficacy is good, it will increase students' critical thinking skills in science.